Peningkatan Kompetensi Strategis Siswa Melalui Model Pembelajaran Conceptual Understanding Procedures - Adriyanto Adriyanto; Dewi Pramita; Abdillah Abdillah; Syaharuddin Syaharuddin; Mahsup Mahsup; Eka Fitriani (Unversitas Muhammadiyah Mataram, 2019)
Abstract: This study aims to determine the effectiveness of conceptual understanding procedures learning model to students' strategic competencies taken from student post-test results. The study was included in quasi Experimental Design research involving 41 students consisting of two classes taken from five classes with porposive sampling techniques. The data collection technique used is a test instrument with a significant level of 5%. The results showed that the average strategic competency ability of experimental class students was 61.7, while the average strategic competency ability of control class students was 51. Based on data analysis from the t-test hypothesis that has been done, the results showed t-count > t-table (2.43 > 1.69) so that Ho was rejected and Ha accepted. Therefore, it can be concluded that the Conceptual Understanding Procedures learning model is effective against the strategic competencies of students in the material of building flat-sided rooms in grade VIII junior high school.Abstrak: Penelitian ini bertujuan untuk mengetahui efektifitas model pembelajaran Conceptual Understanding Procedures terhadap kompetensi strategis siswa yang diambil dari hasil post-test siswa. Penelitian ini termasuk dalam penelitian Quasi Eksperimental Design yang melibatkan 41 siswa yang terdiri dari dua kelas yang diambil dari lima kelas dengan teknik porposive sampling. Teknik pengumpulan data yang digunakan adalah instrumen tes dengan taraf signifikan 5%. Hasil penelitian menunjukkan, rata-rata kemampuan kompetensi strategis siswa kelas eksperimen sebesar 61,7, sedangkan rata-rata kemampuan kompetensi strategis siswa kelas kontrol sebesar 51. Berdasarkan analisis data dari uji hipotesis uji-t yang sudah dilakukan, hasilnya menunjukkan t-hitung > t-tabel (2,43 > 1,69) sehingga Ho ditolak dan Ha diterima. Oleh sebab itu, dapat disimpulkan bahwa model pembelajaran Conceptual Understanding Procedures efektif terhadap kompetensi strategis siswa pada materi bangun ruang sisi datar kelas VIII SMP.